Smart Teachers in Building Students’ Character in 4.0 Industrial Revolution Era - Ningsih, Tutuk (International Conference of Moslem Society, 2019)
A teacher is one element that is very vital in running education, which is one of the most important aspects in the 4.0 industrial revolution era. For that reason, the quality of a teacher will be a very contributing factor to the success of education in. In such an era, smart teachers should be equipped with innovations and creativity and are able to make a fun and interactive teaching and learning process. They are also expected to be able to encourage students to be active to participate in the learning process in order to make sure that the objectives of learning can be achieved. In this era, teachers’ role in developing students’ character is significant. This is because students will face this millennial era, which come a long with all chances and threat, and they should equip themselves with good characters as well as specific skills needed. The broad use of the internet will of course give some impacts to students’ characters, either the good and the bad ones. For that reason, character building at schools is really needed to avoid students from losing their identity. Building students’ character needs smart teachers who have four competencies, i.e. professional, paedagogic, personal, and social competencies. Having such competencies, teachers are expected to be able to build students’ good character and can help students to have the characters which go along with parents’ and community’s expectations. The efforts to build students’s characters can be realized through intra and extra-curriculair activities to facilitate students in developing the 18 characters as stated by Education and Culture Ministry of Indonesia.